Developing a Customer-Focus Approach to Marketing of Library and Information Services - Gupta, Dinesh K.; Jambhekar, Ashok (DESIDOC Journal of Library & Information Technology, 2003)
Philosophically, users are the central entity in all types of libraries. Thecharacteristics of the user body make up an essential and indeed central elementin the development of library services. In ways that are now familiar from serviceindustry contexts, we need to incorporate elements of client-orcustomer-centeredness in our approaches to serve users. Users also expectrecognition, attention, and appreciation for their individual needs and have desirefor self-expression. In such environment, the library system triumphs, which hasmore customer-focus approach in serving and meeting these needs and thelibrary becomes market driven in the real sense. The customer-focusorganisations accept that marketing issue is philosophical and also a strategicone. They are concentrating on developing customer orientation. Their focus ison distinctive competencies, value delivery, customer-defined quality, relationshipmanagement, and a customer-focused organisational culture. In the presentpaper an attempt has been made to clarify, what customer-focus approach is allabout?; how quality, customer service and marketing are closely related to eachother in customer-focus approach?; and how customer-focused culture can bedeveloped in library and information centres. http://dx.doi.org/10.14429/dbit.22.3.3564